Multiplex ligation-dependent probe amplification (MLPA) assay for the detection of CYP21A2 gene deletions/duplications in Congenital Adrenal Hyperplasia: First technical report - Concolino, Paola; Mello, Enrica; Toscano, Vincenzo; Ameglio, Franco; Zuppi, Cecilia; Capoluongo, Ettore (Clinica chimica acta, 2009)
More than 90% of the cases of Congenital Adrenal Hyperplasia (CAH) are associated with mutations in 21-hydroxylase gene ( CYP21A2). Up to now, large CYP21A2 rearrangements have been mainly detected by Southern blot analysis, although more rapid methods have been alternatively proposed. In this paper, we report the use of a multiplex ligation-dependent probe amplification (MLPA) method for easy and rapid detection of deletions/duplications in the CYP21A2 gene. We collected 18 CAH Italian patients previously analyzed by gene sequencing and Southern blot technique. In addition, a prenatal diagnosis study was performed. Of the 7 known subjects with CYP21A2 deletions and 2 with gene duplications previously characterized in our laboratory, all were successfully identified by the MLPA analysis. In the prenatal diagnosis study, the MLPA assay was able to identify the presence of a CYP21A2 gene duplication in the fetus, as well in other two family members. MLPA analysis represents a simple, rapid and sensitive tool for the detection of CYP21A2/CYP21A1P deletions/duplications in CAH molecular diagnosis. Compared to Southern blot, MLPA may be considered a high throughput analysis, allowing the simultaneous study of several samples in the same experiment and the investigation of both gene ( CYP21A2) and pseudogene ( CYP21A1P) in each patient.